Evaluation of Nurses Practices toward Patients with Tracheostomy in Respiratory Care Units in Baghdad Teaching Hospitals - Sabah Abass Ahmed (Kufa Journal for Nursing Sciences)
Objectives: The study aims to evaluate the nurse's practices toward patients with Tracheostomy in respiratory care units, and to find out the significant differences between their practices and some variables.